Dust sampling in WEST and tritium retention in tokamak-relevant tungsten particles. (August 2020) - Peillon, S.; Dougniaux, G.; Payet, M.; Bernard, E.; Pieters, G.; Feuillastre, S.; Garcia-Argote, S.; Gensdarmes, F.; Arnas, C.; Miserque, F.; Herlin-Boime, N.; Grisolia, C.; et al.
Highlights: Dust sampling have been done after C2 campaign in WEST tokamak. Micrometer tungsten particles with spherical shape were collected. Surrogate tungsten powder was used for tritium retention measurements. Self-charging rates of tritiated tungsten dust were estimated with Monte-Carlo calculations. Abstract: The paper presents complementary approaches based on experimental and numerical works to address the behavior of tokamak-relevant tungsten particles loaded with tritium. Sampling of particles inside the WEST tokamak have been realized thanks to an in situ particle collection system called Duster Box. This method allowed to identify various types of tungsten particles among them spherical shaped micro-particles between 5 µm and 30 µm in diameter. Based on these results a surrogate tungsten powder has been provided by means of spheroidization process and sieving method. Moreover, the powder tritium retention capacity was measured and specific activities of 90 MBq.g −1 and 280 MBq.g −1 were obtained for particles with 17 µm and 11.5 µm median diameters, respectively. Considering such tritium activities trapped in the particles, Monte-Carlo simulation were performed to estimate the electrostatic self-charging rates and the corresponding electrical charge carried by the radioactive tungsten dust. The results of these experiments provide robust data for the assessment of the dispersion of toxic/radioactive material in the environment that could follow a loss of containment.